Design and synthesis of some new benzene sulfonamides and related derivatives targeting carbonic anhydrase enzymes - Mazin Abed Alghani Najm.; Walaa Ramadan Mahmoud (2022)
. . (SLC-0111). IVa-d) (XIIa-c Va-d) (XIIIa-c Va-d) (XIVa-c . . I II IX XII IVa) IVb IVc IVd Vd XIIa (XIIc hCA I, II SLC-0111. 60 (XIVb) CDK2. . : . : . . SLC-0111 . . : . . : 3. 1. : . 3. 2. : (XIVb) CDK2 . (IVa IVb IVc IVd Vd XIIa (XIIc hCA I, II SLC-0111. (XIVb) . 3. 3. : 3. 3. 1.: : 3. 3. 1. 1. : (IVb IVc XIIa) (hCA) . (IVb IVc) hCA I (XIIa) hCA II. 3. 3. 1. 2. CDK2: (XIVb) CDK2 . 3. 3. 2. : (IVb IVc XIIa XIVb) SWISS ADME . . : 4. 1. : 14 6 15 . 4. 2. : . 4. 3. : CDK2 SWISS ADME . 5. : .
Thesis (Ph.D)-Cairo University,2022.
Bibliography: p. 129-156.
Keywords: Sulfonamides and Related Derivatives Targeting